Wireless sensor network design by lifetime maximisation: an empirical evaluation of integrating major design issues and sink mobility. (2016) - Keskin, M. Emre; Altınel, İ. Kuban; Aras, Necati; Ersoy, Cem
The collective behaviour of wireless sensors provides a network to monitor a region. Most of the applications require a sufficiently long network operation, which makes the efficient management of the available energy resources an important issue. It is a known phenomenon that sensors communicating directly with a sink deplete their energy faster than others. Hence, some of the sinks are disconnected from the rest of the network even though most of the sensors are still functional. A possible remedy is to balance the relaying load of the sensors using mobile sinks and controlling their mobility. In this work, we consider three major design issues, i.e., coverage, locating mobile sinks, and routing sensor-to-sink data within a unified framework and develop mixed-integer linear programming formulations to maximise the network lifetime. We also numerically compare the new models and demonstrate the improvement obtained by controlling the sink mobility and integrating various design issues.